Erythrosine-induced hepatic biomarkers and histopathological changes in male rats: protective effects of lycopene and anthocyanin - Qahl, Safa H.; Alqahtani, Fatimah A.; Al-Nahari, Haleema; Alghamdi, Fawzyah A.; Khouja, Fatimah H.; Khouja, Amna H. (Frontiers in Pharmacology, 2026)
This study aimed to explore and reassess the safety and efficacy of the synthetic food dye erythrosine (ERY) with respect to the hepatic biomarkers and histological changes in male adult rats as well as possibly alleviate the effects of ERY through administration of lycopene (LYC) and anthocyanin (ANC). Sixty adult male rats were randomly distributed into six experimental groups as follows: control, LYC (5 mg/kg), ANC (200 mg/kg), ERY (20 mg/kg), ERY + LYC, and ERY + ANC. After 3 and 6 weeks of treatment, ERY (20 mg/kg) produced marked biochemical and hepatic injuries. ERY significantly reduced the total protein (from 6.93 g/dL in control to 5.33 g/dL) and albumin (from 2.65 to 1.77 g/dL, p < 0.050), whereas LYC and ANC co-administration improved these values compared to ERY alone (p < 0.050). ERY was also found to elevate the total cholesterol, triglycerides (TG), and low-density lipoprotein (LDL) values relative to the control, whereas both LYC and ANC lowered LDL and TG levels compared to the ERY-treated rats. The liver injury markers were strongly increased by ERY, with alanine transaminase (ALT) increasing from 14.00 to 23.95 U/L, aspartate transaminase (AST) increasing from 41.54 to 52.90 U/L, and gamma-glutamyl transferase (GGT) increasing from 6.24 to 8.64 U/L. Cotreatment with LYC or ANC was seen to significantly reduce ALT, AST, and GGT (p < 0.050). The total bilirubin increased significantly in the ERY group but was restored to near-control levels with both LYC and ANC. Histologically, ERY produced moderate-to-severe focal hepatic degeneration, including hepatocyte cytoplasmic vacuolation (score 2–3), nuclear chromatin clumping (score 2), focal necrosis (score 2), and leukocytic infiltration (score 2–3); LYC and ANC markedly ameliorated these lesions, reducing the pathological scores to 0–1, while restoring the hepatic cords, sinusoids, and nuclear morphology to near-normal or normal appearance by week 6. Collectively, ERY impacted the hepatic chemistry and functionality with considerable effect on the histological appearance of the hepatic tissues in rats, while ANC and LYC resourcefully attenuated these adverse effects.